Effect of different priming methods and temperatures on seed dormancy breakage and germination of Pulicaria gnaphalodes (Vent.) Boiss - Elham Harati; Seyyed Gholamreza Moosavi; Fatemeh Nakhaei; Mohamad Javad Seghatoleslami (علوم و فناوری بذر ایران)
Seed germination is the first and most sensitive developmental stage in the plant life cycle and the key process in seedling emergence. On the other hand, one of the major barriers to optimum use of medicinal plants outside the natural habitat is limited level of seed germination and seed dormancy. Hence in order to find the best priming and temperature treatment to dormancy breaking and seed germination of medicinal plant seed Pulicaria gnaphalodes (Vent.) Boiss a factorial experiment based on the completely randomized design with four replications and two factors was conducted in Islamic Azad University, Birjand branch in 2017. The first factor of priming type is 11 levels included in potassium nitrate 2% treatment at two times of 24 and 48 hours, gibberellic acid (0, 250 and 500 mg/ l) at two times of 24 and 48 hours, and stratification (7, 14 and 21 days). The second factor was temperature at three levels (15, 20 and 25 °c). The results showed that highest germination rate and percent germination were related to stratification at 7 and 21 days at 25 °c and maximum seedling length, plumule length, radicle length, radicle/plumule length ratio, wet weight of seedling, dry weight of seedling, percent germination, germination rate, longitudinal index seed vigor, weight index seed vigor related to 21 days wet temperature and 15°c. Therefore, 21 days stratification and temperatures of 15 and 25 °c were the best priming and temperature treatments to dormancy breaking and seed germination of medicinal plant seed Pulicaria gnaphalodes.